1976
DOI: 10.1042/bj1530329
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for an allosteric model for ribonuclease

Abstract: Evidence is presented from three experimental systems to support the allosteric model of Walker et al. (1975) (Biochem. J. 147, 425-433) which explains the substrate-concentration-dependent transition observed in the RNAase (ribonuclease)-catalysed hydrolysis of 2':3'-cyclic CMP (cytidine 2':3'-cyclic monophosphate). 1. Kinetic studies of the initial rate of hydrolysis of 2':3'-cyclic CMP show that the midpoint of the transition shifts to lower concentrations of 2':3'-cyclic CMP in the presence of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…At relatively low concentrations of this type of substrate, in an aqueous environment, the only significant route is that of hydrolysis, and a hyperbolic substrate concentration dependence is usually obtained. However, working at high substrate concentrations, Walker et al (4,5) observed that at pH 7.0, the dependence of the rate of hydrolysis with substrate concentration shows a nonhyperbolic behavior: there is a drop at about 25 mM to 30 mM CϾp 1 followed by a second rise and then a gradual decline, which they interpreted by an allosteric model in which there is a substrate-dependent change in the equilibrium between three pre-existing enzyme conformations, one of which inactive. Later, Piccoli and d'Alessio (6) also showed deviations from hyperbolic kinetics for RNase A with CϾp, but only at a low substrate concentration.…”
mentioning
confidence: 99%
“…At relatively low concentrations of this type of substrate, in an aqueous environment, the only significant route is that of hydrolysis, and a hyperbolic substrate concentration dependence is usually obtained. However, working at high substrate concentrations, Walker et al (4,5) observed that at pH 7.0, the dependence of the rate of hydrolysis with substrate concentration shows a nonhyperbolic behavior: there is a drop at about 25 mM to 30 mM CϾp 1 followed by a second rise and then a gradual decline, which they interpreted by an allosteric model in which there is a substrate-dependent change in the equilibrium between three pre-existing enzyme conformations, one of which inactive. Later, Piccoli and d'Alessio (6) also showed deviations from hyperbolic kinetics for RNase A with CϾp, but only at a low substrate concentration.…”
mentioning
confidence: 99%
“…Previous studies (Walker et al, 1975(Walker et al, , 1976) have demonstrated that conditions that favour the binding of ligands to the allosteric sites (e.g. increased concentrations of the substrate or its analogues) favour a shift in the equilibrium towards form F of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…173 transition region decreases with increasing pH until the transition becomes a plateau at pH10.6. Data were insufficient for reliable estimates of APE, the number of ligand molecules involved in the E-to-F transition (Walker et al 1976), but AP, appeared to decrease from pH 7.13 to pH 10.0. Effect of lysine carbamoylation on plots ofv versus [S] Plots of v versus [SI for unmodified enzyme and enzyme carbamoylated for 2, 7 and 20min are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are ribonucleotide triphosphate reductase (26-28), pancreatic ribonuclease (29)(30)(31), and wheat hexokinase Ll (32). In all these cases there are evidences that the enzymes are single polypeptide chains, but unequivocal proof that they do not oligomerize during the assay has not been reported.…”
Section: Discussionmentioning
confidence: 99%